2020
DOI: 10.1002/ppul.24997
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative pulmonary complications in children with severely compromised pulmonary function secondary to severe scoliosis

Abstract: Objectives After corrective surgery for scoliosis, postoperative pulmonary complications lead to increases in morbidity, length of hospital stay (LOS) and mortality. This study aimed to identify associations with such respiratory complications, and to assess the utility of noninvasive ventilation (NIV) in children with severe scoliosis Methods This retrospective cohort study included all children aged ≤17 years who underwent spinal surgery for scoliosis between January 2009 and January 2012 at a quaternary ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Although a previous study reported that preoperative PSG did not predict prolonged postoperative ventilator use after scoliosis surgery[ 20 ], a recent study revealed that before severe scoliosis repair surgery, severely compromised respiratory function could be confirmed in advance through PSG and overnight TcCO 2 monitoring, both of which measure hypoventilation. According to the PSG and TcCO 2 results, there was an advantage of the timely use of a non-invasive ventilator that could avoid tracheostomy[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a previous study reported that preoperative PSG did not predict prolonged postoperative ventilator use after scoliosis surgery[ 20 ], a recent study revealed that before severe scoliosis repair surgery, severely compromised respiratory function could be confirmed in advance through PSG and overnight TcCO 2 monitoring, both of which measure hypoventilation. According to the PSG and TcCO 2 results, there was an advantage of the timely use of a non-invasive ventilator that could avoid tracheostomy[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disordered breathing (SDB) is known to be a common cardiopulmonary complication in PSW[ 3 ]. The most two representative causative factors are obstructive sleep apnea (OSA) due to airway narrowing caused by obesity and hypotonia[ 3 , 4 ], and hypoventilation due to progressive deterioration of the restrictive pattern of the lungs caused by scoliosis[ 3 , 5 , 6 ]. Respiratory symptoms appear from infancy, and OSA is known to be a major contributing factor after 2 years of age[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations